in Late Diagnosed Congenital Hearing Loss with Delayed Speech: A Case Report - Maulana, Muhammad Sobri (Aulad: Journal on Early Childhood, 2020)
Introduction : Hearing impairment in children happened in 6 per 1000 newborn in developing country. The etiology of most of those case is unknown as stated by WHO that 60% of children hearing loss caused by genetics. Aim : This condition could lead to delayed speech in children. Method : A-6-years-old children referred to ENT department with delayed speech and bilateral profound sensorineural hearing loss to get a choclear implant. Result : Her condition suspected to be caused by rubella infection during pregnancy. She was already using hearing aid occasionaly and her mother complain that she still couldn’t hear effectively. The comprehensive management of infant with congenital hearing loss could be diagnosed early by applying hearing screening on all newborns at 1 month of age based on EHDI recommendation. This case represents the society low awareness and diagnostic tools limitation of congenital hearing loss prevention in Indonesia. Therefore, we suggest newborn hearing screening on all high-risked babies based on the risk factor stratification. Habilitation strategy for this patient includes auditory-verbal therapy. In order to maximize the benefit, parents are required to give maximum contribution to each therapy session. The therapy compliance becomes the important parameter in outcome optimization. Early diagnosis and intervention is the key to the management of congenital hearing loss. The EHDI programs provide recommended timeline for newborn hearing screenings, diagnostic examinations, and early interventions. The treatment consists of conventional hearing aid and cochlear implantation, combined with speech and language therapy in an appropriate educational environment, to promote development of communication and educational achievements